All together now: building resilient citizen energy communities through collaborative learning - Paul Tobin; Breffní Lennon (Environmental Research: Energy)
As the energy transition deepens, a key component of this effort has been the advancement of citizen energy communities (EC) which are vital for fostering the innovation needed to achieve net zero. While notable effort has been made to capture the perspectives of energy cooperatives, little attention has been paid to the shared perspectives of energy cooperatives and the energy distribution system operators they must engage with when establishing an energy community. This paper seeks to address this by examining how collaborative learning, a participatory approach where stakeholders share knowledge and experiences to identify challenges and co-develop strategies, can help practitioners identify and better understand the key barriers and drivers to citizen energy community formation. Drawing from original research conducted across four distinct EC situated in four European countries, it outlines how a living lab, a real-world, user-centred research environment for testing and refining energy solutions, was utilised to understand the motivations that underscore people’s attitudes towards, and participation in, a ‘community’. Findings indicate that togetherness—expressed through social and functional relationships—is a foundational component of EC, supported by key factors such as context, values, and needs. The study also highlights major challenges, including a lack of social democracy, regulatory issues, and uncertainty about benefits, with social engagement emerging as the most effective strategy for building resilience, or the capacity of communities to adapt and sustain participation. The paper also engages with the wider debates found within this journal on the deployment of living labs and their applicability as a tool for socio-technical innovation that can empower EC and build greater resilience amongst stakeholders.